Open educational practices and resources based on social software: UTPL experience - Piedra Pullaguari, N. (2009)
Open Educational Resources (OER) are a direct reaction to knowledge privatization; they foment their exchange to the entire world with the aim of increase the human intellectual capacity. In this document, we describe the committment of Universidad Técnica Particular de Loja (UTPL), Ecuador, in the promotion of open educational practices and resources and their impact in society and knowledge economy through the use of Social Software. © 2009 IEEE.